Impact of Intubator's Training Level on First-Pass Success of Endotracheal Intubation in Acute Care Settings: A Four-Center Retrospective Study - Jung-Heon Kim; Jae-Yun Jung; Joong-Wan Park; Se-Uk Lee; Meong-Hi Son; Jeong-Yong Lee (MDPI AG, 2022)
(1) Background: First-pass success (FPS) of endotracheal intubation is more challenging in children than in adults. We aimed to identify factors associated with FPS of intubation in acute care settings. (2) Methods: We analyzed data of children aged <10 years who underwent intubation within ≤24 h of arrival at four Korean emergency departments (2016-2019). Variables were compared according to FPS. A logistic regression was performed to quantify the association of factors with FPS. An experienced intubator was defined as a senior resident or a specialist. (3) Results: Of 280 children, 169 (60.4%) had FPS. The children with FPS were older (median age, 23.0 vs. 11.0 months; p = 0.018), were less frequently in their infancy (36.1% vs. 50.5%; p = 0.017), and were less likely to have respiratory compromise (41.4% vs. 55.0%; p = 0.030). The children with FPS tended to be more often intubated by experienced intubators than those without FPS (87.0% vs. 78.4%; p = 0.057). Desaturation was rarer in those with FPS. Factors associated with FPS were experienced intubators (aOR, 1.93; 95% CI, 1.01-3.67) and children's age ≥12 months (1.84; 1.13-3.02). (4) Conclusion: FPS of intubation can be facilitated by deploying or developing clinically competent intubators, particularly for infants, in acute care settings.